PGC‐1α regulates the expression and activity of IRF‐1. Issue 4 (15th April 2015) - Lu, Huading; Zhu, Lei; Lian, Liyi; Chen, Mingwei; Shi, Dehai; Wang, Kun
Abstract: Interferon regulatory transcription factor 1 (IRF‐1) regulates downstream signals of tumor necrosis factor α (TNF‐α). The activity of IRF‐1 is mediated by Jak/Stat signaling pathway. In this study, we found that PPAR γ coactivator‐1α (PGC‐1α) is able to suppress the induction of IRF‐1. Treatment with TNF‐α in MC3T3 cells leads to a sustainable increase in the expression of IRF‐1 and its target gene cyclooxygenase 2 (COX‐2). In contrast, TNF‐α treatment led to a sustainable reduction in expression of PGC‐1α. Interestingly, we found that overexpression of PGC‐1α attenuated the induction of IRF‐1 and COX‐2. However, silence of PGC‐1α exacerbated the induction of IRF‐1 and COX‐2. Importantly, we found that the effect of PGC‐1α on repressing IRF‐1 expression and activity is facilitated by the reduction in phosphorylation of STAT1 at position 727 (S727P), an essential transcriptional activator of IRF‐1. Finally, we found that calyculin A, a pharmacological inhibitor of protein phosphatase 2A (PP2A) and PP1 abolishes the repression of STAT1 phosphorylation mediated by PGC‐1α, suggesting a new mechanism of PGC‐1α in regulating STAT1/IRF‐1 pathway. © 2015 IUBMB Life, 67(4):300–305, 2015